Training in metacognitive strategies for students’ vocabulary improvement by using learning journals (2015)
This study examined the effects of metacognitive strategies to help beginning young learners with difficulties increasing and retaining vocabulary. This was a qualitative study in which participants first went through metacognitive strategy instruction to provide awareness of learning strategies. Following this instruction, students underwent a set of five interventions based on the cognitive academic language learning approach instructional model. These interventions, together with journaling progress, were used to train them in the use of the metacognitive strategies planning, monitoring, and evaluating. The findings showed that metacognitive strategy training has positively contributed to vocabulary acquisition skills, as participants were able to raise consciousness about some learning strategies and the use of metacognitive strategies to increase their vocabulary learning.Este estudio examinó el efecto de las estrategias meta-cognitivas para ayudar a estudiantes con dificultades para aumentar y retener vocabulario en inglés. Este fue un estudio cualitativo, en el cual se instruyó en el uso de estrategias meta-cognitivas proporcionando el conocimiento de estrategias de aprendizaje. Luego, se aplicó un conjunto de cinco intervenciones basadas en el método académico cognitivo para la enseñanza de lenguas. Estas intervenciones, junto con el uso de diarios, se utilizaron para entrenarlos en el uso de estrategias meta-cognitivas. Los resultados mostraron que el entrenamiento de estrategias meta-cognitivas ha contribuido positivamente en la adquisición de vocabulario, ya que los participantes fueron capaces de propiciar el conocimiento acerca de algunas estrategias de aprendizaje y el uso de estrategias meta-cognitivas para aumentar su aprendizaje de vocabulario.